Atrazine: a lively chemical journey - Dornbrack, Kevin (Environmental Humanities, 2023)
Atrazine is a widely used pesticide, particularly popular in corn plantations for its herbicidal properties of killing and preventing the growth of certain weeds and grasses. Evidence of its neurotoxicity, hormone disruption and reproductive toxicity led the EU to ban the chemical in 2003. Despite long standing evidence of its harm, South Africa continues to use atrazine, the majority of which is imported from the EU. Drawing on South Africa as a case study, I illustrate Atrazine's unique journey through South Africa's political economic landscape, interpreted in relation to those of the USA and EU, highlighting that problems of chemical pollution are political as much as they are molecular. In this project, I have employed biochemical, epidemiological, historical, social and political scientific approaches to form an interdisciplinary understanding of atrazine's biochemical, ecological, and economic effects; how its harm lands unevenly on poor and marginalized people, often in the global south; and how commercial and governmental structures enable and maintain its use. This interdisciplinary understanding of atrazine's uneven effects as well as its varied socio-political figurations illustrates how and why regulatory processes have proved vastly inadequate to curtail the chemical pollution caused by atrazine and many other pesticides. The results of this research should hopefully serve as a case study and cautionary tale of globally increasing and unevenly experienced chemical exposure. This project argues that effects of atrazine within their political and historic contexts should be considered a form of unspectacular violence, that slowly but persistently degrades quality of life. By tracing the networks of atrazine's chemical relations, this project illustrates that the molecular is always political.